The Concept of Student’s Islamic Education Online Learning During Post-Pandemic - Pranajaya, Syatria Adymas; Rijal, Syamsul; Silahuddin; Fitriyah, Husnatul (International Journal of Education, Language, and Social Science, 2023)
Religious education is a basic effort that has been prepared and planned to process student learning, by religious principles so that they can control themselves, have good morals, and know religious principles. In the post-Covid-19 pandemic, it is hoped that the education aspect can catch up due to the pandemic, and can improve in all lines of education, especially Islamic education, because there is no stopping to study. In any way, we can still learn, one of which is by using online learning. The method used in this research article is a method of literature study and content analysis. The systematics of Islamic education consists of 3 main materials that can be developed to form human beings who are noble, virtuous, and useful for others, namely Faith, Worship, and Morals. This must be supported by strategies for learning Islamic Education during the pandemic and post-pandemic times. The use of strategies in learning is important because it has certain goals to be achieved for what teachers do in the teaching and learning process of Islamic education. Many learning strategies can still be applied post-pandemic in Islamic Education, such as affective strategies, inquiry strategies, expository strategies, problem-based learning strategies (PBL), cooperative strategies, and contextual teaching and learning (CTL) strategies. The learning strategy is the real action of the teacher or the practice of the teacher carrying out teaching in a certain way which is considered more effective and efficient.